2008
DOI: 10.1089/jwh.2007.0473
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Program Directors' Perceptions of Women's Health Education: A Gap in Graduate Medical Education Persists

Abstract: Despite national guidelines endorsing women's health education, a large discrepancy persists between what PDs believe their residents should master and what they estimate their residents actually master. This study suggests a need for substantial improvements in internal medicine residency training to adequately prepare residents to care for women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 10 publications
(9 reference statements)
1
20
0
Order By: Relevance
“…[1][2][3][4][5] Additional studies among IM residency graduates, 6,7 as well as surveys of program directors, 8,9 have reported similar findings.…”
mentioning
confidence: 85%
“…[1][2][3][4][5] Additional studies among IM residency graduates, 6,7 as well as surveys of program directors, 8,9 have reported similar findings.…”
mentioning
confidence: 85%
“…Repeated for a final time in 2001, by the Society for Women's Health Research, there was ultimately an increase to 44% of medical schools offering WH curriculum. 2,5 This evidence validates that many students are not getting exposure to women's health early in their medical careers 8 and are lacking a significant experience unless ultimately choosing a residency in obstetrics and gynecology. Early exposure heightens curiosity, learning, and interest in the field and ultimately demonstrates to students and residents that a career in women's health can be achieved through both family medicine and internal medicine, 3 and most comprehensively after the successful completion of a fellowship.…”
mentioning
confidence: 81%
“…Midlife should be a time for women to enjoy and improve their health, and WH providers are crucial in achieving and maintaining this lifestyle, as they have focused training that is not affordable by residency training or continuing medical education (CME) classes alone. 20 Multiple studies have shown that gaps in WH training remain, 8,20 and WH specialty providers poses a unique skill set that includes some or all of the following: knowledge of current literature on hormone therapy (HT) and the risk/benefit classifications of prescribing HT; following Pap results; performing office-based minor procedures such as colposcopy, cervical polyp removal, or IUD insertion; medically managing abnormal uterine bleeding; reading bone density scans and prescribing osteoporosis treatment; managing low libido; managing urinary incontinence; and contraception management and a unique understanding of how gender-based medicine plays a role in the management of chronic conditions such as diabetes, heart disease, and depression. 21 Moreover, WH specialty providers have a broad understanding of diseases that are more common in women, such as autoimmune conditions, thyroid disorders, rheumatologic conditions, and chronic pain syndromes; breast cancer survivors as well as those that carry genetic mutations; and cardiovascular conditions.…”
Section: Provider Skillsmentioning
confidence: 99%
See 2 more Smart Citations